2014
DOI: 10.1002/bies.201400044
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interaction analysis of point mutations enables interrogation of gene function at a residue‐level resolution

Abstract: We have achieved a residue-level resolution of genetic interaction mapping – a technique that measures how the function of one gene is affected by the alteration of a second gene – by analyzing point mutations. Here, we describe how to interpret point mutant genetic interactions, and outline key applications for the approach, including interrogation of protein interaction interfaces and active sites, and examination of post-translational modifications. Genetic interaction analysis has proven effective for char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 75 publications
(110 reference statements)
0
7
0
Order By: Relevance
“…The first pE-MAP covered 53 budding yeast point mutants in RNA polymerase II (RNAPII), crossed against a library of 1,200 deletion and knockdown mutants 89 . This study revealed that pairs of residues that exhibited similar genetic interaction profiles were typically close in space, whether they resided in the same or different RNAPII subunits 89 , 90 . Several early DMS studies revealed similar patterns for the pairwise genetic interactions between point mutants 92 94 .…”
Section: Genetic and Chemical–genetic Interactionsmentioning
confidence: 85%
See 1 more Smart Citation
“…The first pE-MAP covered 53 budding yeast point mutants in RNA polymerase II (RNAPII), crossed against a library of 1,200 deletion and knockdown mutants 89 . This study revealed that pairs of residues that exhibited similar genetic interaction profiles were typically close in space, whether they resided in the same or different RNAPII subunits 89 , 90 . Several early DMS studies revealed similar patterns for the pairwise genetic interactions between point mutants 92 94 .…”
Section: Genetic and Chemical–genetic Interactionsmentioning
confidence: 85%
“…These results indicated that genetic interactions provide a high level of resolution and allow the dissection of multifunctional proteins into regions that are functionally and physically connected to other factors. Spurred by these findings, the E-MAP technology was extended to screen entire libraries of point mutations in a set of related proteins to generate point mutant E-MAPs (pE-MAPs) 89 , 90 . Quantitative SGA screens have also included large numbers of point mutations; however, these have generally been chosen on the basis of their phenotype as temperature-sensitive alleles of essential genes, rather than systematic mutations of a specific protein or complex 68 , 69 .…”
Section: Genetic and Chemical–genetic Interactionsmentioning
confidence: 99%
“…Remarkably, though Sub1 is an elongation factor, the SUB1 deletion mutant is resistant to 6AU because the IMD2 gene is constitutively expressed due to defects in the transcription start site selection. On the contrary, in isogenic wt cells, IMD2 is induced only upon 6AU treatment [ 22 , 26 , 52 ]. Interestingly, we showed that Sub1 influences IMD2 transcription elongation, thereby affecting the novo synthesis of IMD2 after 6AU treatment [ 26 ].…”
Section: Resultsmentioning
confidence: 99%
“…With the completion of sequencing for many organisms, especially that of yeast, the ability to interrogate the functional implications of individual genes to a phenotype has revolutionized genome-based studies 25 51 . Large-scale genetic interaction assays have made it possible to model the lives of eukaryotic organisms in order to identify the complicated connectivity among genes and study how this interactivity constitutes a network that determines the phenotype 52 53 ; in this case, chemotherapeutic resistance. The study of genetic interactions has gained momentum, and the revelation of the ‘interactome’ 54 has shed light on how multiple components can be regulated concurrently.…”
Section: Discussionmentioning
confidence: 99%